Emotional intelligence and learning motivation among first year university students in Kota Samarahan - Sharifah Munira, binti Sibin (Universiti Malaysia Sarawak (UNIMAS), 2015)
This study explored the relationship between emotional intelligence and learning motivation. This study also explored the demographics differences by gender and ethnic among first year university students in Kota Samarahan. This study used quantitative method. Shutte‟s Self- Reported Inventory (1998) that comprised of 33 items was used to measure students‟ emotional intelligence while model of learning motivation was measured using instrument by Lepper, Corpus and Iyengar (2005) that comprised of 33 items .The results were analyzed using descriptive data analysis and inferential data analysis. Finding showed emotional intelligence to be highly correlated to learning motivation, where the correlation was found to be moderately strong. Independent T-test found no difference in emotional intelligence and learning motivation by gender.One Way Anova found no difference in emotional intelligence and learning motivation by ethnic.